Diseño de un plan de comunicación para la apropiación de los principios de economía social y solidaria, bajo la experiencia de fincas agroecológicas, por parte de los habitantes del barrio Argelia Alta. - Campos Naranjo, Santiago Javier (2014)
This is a communication plan based on the agroecological farm experience developed by the Argelia Alta entrepreneur’ association women. In which, the author analyzes the communicative processes developed both within and outside of the partnership, mainly using the participant observation technique. The study seeks to bring the knowledge and dissertation about the Economy Social Solidarity, by parsing from a communicative design that came from the cultural and social community characteristics, who will become the axis in which turns its internal and external future. In this way we come to agree the direct dialog and the active participation of the members involved in the process, such as the fundamental components in the search for the solidarity economic processes, reciprocal and fair consolidation.